Hybrid precoder for massive MIMO systems with coverage constraint - Lingxiao Kong; Shengqian Han; Chenyang Yang (IEEE/CIC International Conference on Communications in China - Workshops (Online), 2015)
Hybrid architecture has been shown to be cost effective for massive multi-input multi-out (MIMO) systems, where analog precoder is used to form narrow beams towards users for data transmission with reduced number of radio frequency chains. However, besides the user-specific data, a wideband massive MIMO system needs to broadcast control signaling intended for all users simultaneously, which requires wide beams to ensure the coverage. In this paper, we study the wideband hybrid precoder for downlink space-division multi-access and orthogonal frequency division multi-access (SDMA-OFDMA) massive MIMO systems, aimed at minimizing the total transmit power of the base station, subject to the coverage constraint of signaling broadcasting and data rate requirements of users. We first derive an upper bound of coverage probability under general spatially correlated channels, with which a hybrid precoder without requiring the iteration between analog and digital precoders is proposed. Simulation results show that under the same data rate requirement and coverage constraint, the proposed hybrid precoder can effectively reduce the total transmit power compared to the method with narrow-beam analog precoder only based on data rate requirements.